Assessing the Performance of Selected Islamic Banks: Evidence from Bangladesh - Akter, Shaharin; Rahman, Md. Mufidur; Subat, Athkia; Rahman, Mohammad Rifat (International Business Education Journal, 2021)
The study aims to assess Islamic banking performance in Bangladesh using fundamental profitability ratios. The secondary data is collected from the financial statements of six respective Islamic Banks in Bangladesh from 2010 to 2019. The study applied the ratio analysis to measure the performance of selected banks. Finally, we used trend analysis to identify the selected ratios and factors’ present and future movement. The ratio analysis concluded that Al-Arafah Islami Bank Limited (AIBL), Export Import Bank of Bangladesh Limited (EXIM), Social Islamic Bank Limited (SIBL), and Shahjalal Islami Bank Limited (SJBL) are slightly in a good position in terms of profitability ratio and management efficiency ratio. In terms of credit risk performance, all banks are in a declining position. SIBL and IBBL are doing well in management ability. However, the study found that AIBL seems to be the most competent in terms of overall performance. Finally, the study is concluded that Islamic banks have a significant contribution to the banking industry of Bangladesh. This study provides clear guidelines about the basic performance indicators, risk, and management efficiency. The investors, stakeholders and the responsible parties should be more concerned while measuring the performance of overall Islamic banking in Bangladesh.